2019
DOI: 10.1002/jbm.a.36753
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination effect to intermediate molecular weight polyethylenimine for gene delivery systems

Abstract: Fluorinated intermediate molecular weight polyethylenimine (FP2ks) with various fluorination degrees was synthesized by conjugation with heptafluorobutyric anhydride and the fluorination effect for gene delivery systems was examined. FP2ks could condense pDNA, forming compact, positively charged, and nano-sized spherical particles. It was thought that their decreased electrostatic interaction with pDNA would be compensated by hydrophobic interaction. The cytotoxicity of FP2ks was increased with the increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…High cytotoxicity represents an obstacle for practical use of PEI when used as a delivery carrier both in vitro and in vivo . Our previous study reported that modification with perfluorinated groups alone had no major effect on the cytotoxicity of PEI, while another study with PEI-Ch copolymers showed decreased toxicity when compared with the parent PEI . We measured cytotoxicity of the copolymers and PEI in B16F10 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High cytotoxicity represents an obstacle for practical use of PEI when used as a delivery carrier both in vitro and in vivo . Our previous study reported that modification with perfluorinated groups alone had no major effect on the cytotoxicity of PEI, while another study with PEI-Ch copolymers showed decreased toxicity when compared with the parent PEI . We measured cytotoxicity of the copolymers and PEI in B16F10 cells.…”
Section: Resultsmentioning
confidence: 99%
“…27 Our previous study reported that modification with perfluorinated groups alone had no major effect on the cytotoxicity of PEI, 12 while another study with PEI-Ch copolymers showed decreased toxicity when compared with the parent PEI. 28 We measured cytotoxicity of the copolymers and PEI in B16F10 cells. The cell viability curves and calculated IC 50 values of all the polymers are summarized in Figure 4 and Table S2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The fluorination of PEI chains was demonstrated to be an efficient strategy to provide enhanced serum stability and cellular uptake, although the degree of substitution has to be precisely controlled to balance cytotoxicity and intracellular delivery issues. [146] In the same framework, the modification of PEI with cholesterol (Chol) along with superhydrophobic perfluorinated (F) moieties (F-PEI-Chol) evidenced to provide enhanced stability, cellular uptake and siRNA silencing, as well as lower cytotoxicity compared to PEI, F-PEI and PEI-Chol. [147] The hydrophobic modification of low molar mass PEI by using short propionic acid (PrA) has been also hypothesized to enhance transfection efficiency.…”
Section: Hydrophobization Of Pei Chainsmentioning
confidence: 99%
“…Studies by Vierling, , Chen, and others , have shown that fluorination of gene vectors by incorporation of fluorocarbon chains into the vector molecules is an effective strategy to enhance their antiserum ability, improve the gene complex stability, and lower the cytotoxicity. The fluorocarbon chains are chemically and biologically inert and feature both hydrophobicity and lipophobicity, which can lead to a high tendency toward phase separation in polar and apolar environments .…”
Section: Introductionmentioning
confidence: 99%